2023
DOI: 10.3390/ma16031122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations on Seismic Behavior of Segmental Assembly of Concrete Filled Steel Tube Piers with External Replaceable Energy-Dissipating Links

Abstract: In order to reduce the damage sustained by the substructure of bridges during an earthquake, reduce economic loss, avoid casualties, and ensure the quick repair of bridges after an earthquake, this paper, inspired by the good seismic performance of the rhombic opening in the shear wall structure, proposes a precast segmental concrete-filled steel tubular (PSCFST) pier with external replaceable energy-dissipating links (EREDL).Through finite element simulation analysis, it can be found that the energy dissipati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…(SCSF) brace to dissipate seismic energy and reduce the residual displacement of RC double-column bridge bents in the transverse direction. The use of sacrificial and replaceable energy-dissipation devices as structural "fuses" [42] has become an important way to enhance the energy-dissipation capacity of double-column or multi-column piers and achieve damage control and functional recovery. In summary, in existing studies on "fuse" structure bridge piers, the replaceable components are mainly arranged in the transverse direction of bridge structures, improving the transversal seismic resistance of double-or multi-column piers.…”
Section: Design Concept and Failure Modes Of The Innovative Dltw-rscbsmentioning
confidence: 99%
See 1 more Smart Citation
“…(SCSF) brace to dissipate seismic energy and reduce the residual displacement of RC double-column bridge bents in the transverse direction. The use of sacrificial and replaceable energy-dissipation devices as structural "fuses" [42] has become an important way to enhance the energy-dissipation capacity of double-column or multi-column piers and achieve damage control and functional recovery. In summary, in existing studies on "fuse" structure bridge piers, the replaceable components are mainly arranged in the transverse direction of bridge structures, improving the transversal seismic resistance of double-or multi-column piers.…”
Section: Design Concept and Failure Modes Of The Innovative Dltw-rscbsmentioning
confidence: 99%
“…Xue et al [41] developed a self-centering slip friction (SCSF) brace to dissipate seismic energy and reduce the residual displacement of RC double-column bridge bents in the transverse direction. The use of sacrificial and replaceable energy-dissipation devices as structural "fuses" [42] has become an important way to enhance the energy-dissipation capacity of double-column or multi-column piers and achieve damage control and functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic performance research of the new precast shear wall system with angle steel connectors: Seismic behavior under the coupling action of axial pressure and cyclic horizontal load [10] Seismic behavior under the coupling action of axial pressure and cyclic horizontal load [26] Influence of infill walls in shear walls on seismic performance Design suggestions for the new shear wall system with angle steel connectors The content of this paper.…”
Section: Research Novelty: Angle Steel Connections With Energy Dissip...mentioning
confidence: 99%
“…Zhou et al [25] proposed a confined prestressed hollow core wall panel that utilizes connection reinforcement, partial grouting, and sleeve connections to link precast components. Some scholars have proposed increasing the seismic performance and comfort of prefabricated structures by installing structural bracings and energy dissipation devices [26,27]. Previous research [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] has demonstrated that, given reliable design and construction practices, common methods for connecting precast concrete shear wall systems can achieve commendable seismic performance.…”
Section: Introductionmentioning
confidence: 99%